Mapping the Intellectual Structure of Mindfulness and Adversity Quotient Research in Teacher Education: Implications for Islamic Teacher Professional Development - Jiraporn Chano; Archrawadee Srijaroon; Bovornpot Choompunuch; Yannapat Seehamongkon; Sudares Sirisittanapak; kanokporn Janatkon; Bahtiar Mohamad (Jurnal Pendidikan Islam, 2026)
Teacher burnout, emotional exhaustion, and declining professional well-being have become significant challenges in contemporary education, particularly in the post-pandemic era. Furthermore, these concerns are equally relevant to Islamic educational institutions, where teachers are expected to demonstrate pedagogical competence, moral integrity, emotional maturity, and spiritual responsibility. In response, mindfulness and Adversity Quotient (AQ) have attracted increasing scholarly attention as psychological resources that support teacher resilience and professional sustainability. Consequently, this study aims to map the development of research on mindfulness and AQ in teacher education and examine its educational relevance for teacher professionalism, resilience, and Islamic teacher development. A bibliometric analysis was conducted using publications indexed in ERIC, Scopus, and Google Scholar between 2020 and 2025. Data were retrieved through Publish or Perish and analyzed using VOSviewer to identify publication trends, citation impact, conceptual structures, and thematic evolution. The findings reveal a substantial increase in research output during the study period, alongside a shift from deficit-oriented themes such as emotional exhaustion and stress management toward resilience, self-compassion, reflective awareness, and well-being. Additionally, keyword co-occurrence analysis identified four major thematic domains: stress management and adversity, emotional regulation and self-compassion, resilience and adaptive capacity, and reflective awareness and well-being. Overall, the findings highlight the growing importance of psychological competencies in supporting teacher professionalism and educational sustainability. For Islamic education, mindfulness and AQ provide relevant conceptual foundations for strengthening holistic teacher development that integrates intellectual, moral, emotional, and spiritual dimensions.